Electrical Measurements in the Laboratory Practice - Bartiromo, Rosario; De Vincenzi, Mario; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book covers the basic theory of electrical circuits, describes analog and digital instrumentation, and applies modern methods to evaluate uncertainties in electrical measurements. It is comprehensive in scope and is designed specifically to meet the needs of students in physics and electrical engineering who are attending laboratory classes in electrical measurements. The topics addressed in individual chapters include the analysis of continuous current circuits; sources of measurement uncertainty and their combined effect; direct current measurements; analysis of alternating current circuits; special circuits including resonant circuits, frequency filters and impedance matching networks; alternating current measurements; analog and digital oscilloscopes; non-sinusoidal waveforms and circuit excitation by pulses; distributed parameter components and transmission lines. Each chapter is equipped with a number of problems. A special appendix describes a series of nine experiments, in each case providing a plan of action for students and guidance for tutors to assist in the preparation and illustration of the experiment.
Electrical Circuits and components -- Direct current circuit analysis -- Uncertainty in electrical measurements -- Direct current measurements -- Alternating current circuit analysis -- Alternating current: special circuits -- Alternating current measurements -- The oscilloscope -- Circuit pulse response -- Transmission line -- App. A: Skin Effect -- App. B: Fourier Analysis.
Keywords: Physics; Electronic circuits; Physical measurements; Measurement; Electronics; Microelectronics; Physics; Measurement Science and Instrumentation; Electronics and Microelectronics, Instrumentation; Electronic Circuits and Devices; Electronic books